The Effect of Alkyl Substituents on the Formation and Structure of Homochiral (R*,R*)-[R2Ga(µ-OCH(Me)CO2R′)]2 Species—Towards the Factors Controlling the Stereoselectivity of Dialkylgallium Alkoxides in the Ring-Opening Polymerization of rac-Lactide - Magdalena Kaźmierczak; Łukasz Dobrzycki; Maciej Dranka; Paweł Horeglad (Molecules)
Building on our previous studies, which have demonstrated that homochiral propagating species—(R*,R*)-[Me2Ga(µ-OCH(Me)CO2R)]2—were crucial for the heteroselectivity of [Me2Ga(µ-OCH(Me)CO2Me)]2 in the ring-opening polymerization (ROP) of racemic lactide (rac-LA), we have investigated the effect of alkyl groups on the structure and catalytic properties of dialkylgallium alkoxides in the ROP of rac-LA. Therefore, we have isolated and characterized the rac-[R2Ga(µ-OCH(Me)CO2Me]2 (R = Et (1), iPr (2) and rac-[R2Ga(µ-OCH(Me)C5H4N]2 (R = Et (3), iPr (4)) complexes, to demonstrate the effect of alkyl groups on the chiral recognition induced the formation of the respective homochiaral species—(R*,R*)-[R2Ga(µ-OCH(Me)CO2Me)]2 and (R*,R*)-[R2Ga(µ-OCH(Me)C5H4N]2. Moreover, we have investigated the structure of (S,S)-[R2Ga(µ-OCH(Me)CO2Me]2 (R = Et ((S,S)-1, R = iPr ((S,S)-2,) and their catalytic activity in the ROP of rac-LA. With an increase in the bulkiness of alkyl substituents on gallium the following can be observed: (a) the tendency for the formation of homochiral complexes decreased, (b) the symmetry of homochiral (S,S)-[R2Ga(µ-OCH(Me)CO2Me]2 (M = Me, Et (S,S)-1), iPr (S,S)-2) changed, and both have resulted in (c) lower or no heteroselectivtity across these complexes in the ROP of rac-LA. Importantly, the results have confirmed the crucial role of the chiral-induced formation of homochiral asymmetric dimers on the heteroselectivity of dialkylgallium alkoxides in the ROP of rac-LA.